Activity of phenolic synthesis pathway enzymes during the development of peduncles clones cashew (Anacardium occidentale L.) - Aline Gonzaga Cunha (2015)
The dwarf cashew apple (Anacardium occidentale L.) is a tropical plant, originated in Brazil, which is fruit species with high potential for fresh consumption and for industrial processing. With the discovery of bioactive compounds in the cashew apple are necessary studies of the activity of enzymes of the synthesis of phenolic compounds, such as phenylalanine ammonia lyase (PAL), UDP-glucose: trans-cinnamate β-D-glycosyltransferase (UGT), flavonol synthase (FLS) and leucoanthocyanidin reductase (LAR). Soon, this study aimed to determine the activity of these enzymes in CCP 76 and BRS 189 dwarf cashew clones in three different stages of maturation, and to establish the phenolic profile in these stages. Reaction products were identified and quantified by LC-DAD. PAL activity decreases with maturation for dwarf cashew clones. UGT enzyme in the CCP 76 clone stage 4 showed the highest enzyme specific activity than in other stages of development for that clone. Whereas BRS 189 clone, the highest activity was in the mature cashew apple. Quercetin synthesis was evidenced in stage 4 for the two clones analyzed. The enzymes involved in the metabolism phenolic behave differently, showing the complexity of this biosynthetic pathway that varies between clones and during the development of cashew apple. Further studies, with mass spectrometer linked HPLC, will elucidate the profile of the compounds present in cashews apple lyophilized for chemical characterization of these in different stages of maturation. Therefore, the understanding of the enzymatic metabolism between the clones and during cashew apple development represent a real potential for the development of new products with functional properties and promotion of human health.